Synthesis of 5′-NAD-capped RNA - Höfer, Katharina; Abele, Florian; Schlotthauer, Jasmin; Jäschke, Andres (Bioconjugate chemistry, 2016)
In prokaryotic organisms, certain regulatory RNAs have recently been found to be linked to the ubiquitous redox cofactor nicotinamide adenine dinucleotide (NAD) at their 5′-ends. Biochemical and structural investigations of this new caplike RNA modification require synthetic access to pure NAD-RNA. Here we report a chemoenzymatic approach to generate 5′-NAD-capped RNA in high yields and purity under mild conditions. This approach uses unprotected 5′-monophosphate RNA synthesized either chemically or enzymatically, 5′,5′-pyrophosphate bond formation by phosphorimidazolide chemistry, and an enzymatic cleanup step. Thus, 5′-NAD-modified RNA can be synthesized independent of length, structure, and nucleotide sequence.